Inferential comprehension differences between narrative and expository texts: a systematic review and meta-analysis - Clinton, Virginia; Taylor, Terrill; Bajpayee, Surjya; Davison, Mark L.; Carlson, Sarah E.; Seipel, Ben (Reading & writing, 2020)
Inferential comprehension is necessary to connect ideas in a text together in a meaningful manner. There have been multiple studies on inferential comprehension involving texts of different genres (narrative and expository), but not a coherent overview of the findings of inferential comprehension by genre. The purpose of this study is to provide a coherent overview by conducting a meta-analysis of the findings of inferential comprehension by genre. A systematic review of the literature yielded 18 reports with 19 independent studies involving 1714 participants in which inferential comprehension was compared by genre. Based on robust variance estimation, scores on measures of inferential comprehension were higher for narrative texts than expository texts ( g = .36, p = .02). This effect did not vary depending on whether inferential comprehension was assessed during or after reading, whether the texts for each genre were matched for readability, whether the reader was an adult or child, and whether the inference connected different ideas in the text (text connecting) or the text to background knowledge (knowledge based). Potential explanations of genre differences in inferential comprehension and future directions for research are discussed.